Kevin's Developmental Psychopathology Potrayal in the Movie " We Need to Talk About Kevin" - Erica, Luisa; Hendrawan, Donny (ULTIMART Jurnal Komunikasi Visual, 2024)
"We Need to Talk About Kevin" is a movie that tells the story of Kevin's life starting from infancy to adolescence, which shows various psychopathological symptoms. Since childhood, Kevin has had various behavioral disorders and has difficulty building a good relationship with his mother, Eva. These behavioral issues worsened until finally, Kevin committed murder against his father, younger sister, and his peers. There are various interactions that can be explained using a perspective from developmental psychopathology to explore every factor in Kevin's life. This research is qualitative research with a phenomenological approach to understand and interpret every aspect of Kevin's life from his childhood and analyze them using theories of developmental psychopathology. The result of this research shows that there are a few factors of developmental psychopathology depicted in the film such as genetics, environmental factors, attachment style, symptoms of maternal depression and stress during pregnancy, as well as parenting styles that play a role in each stage of Kevin's development. In the end, there are also solutions presented to minimize psychopathology in children, namely improving the quality of relationships, family communication, and good co-parenting between father and mother. Through this research, it is hoped that there will be a deeper understanding of the factors in the developmental psychopathology depicted in the film "We Need to Talk About Kevin". Keywords: movie analysis; phenomenological approach; developmental psychopathology